Predictors of clinical or cerebral lesion progression in adult moyamoya angiopathy. (23rd July 2019) - Hervé, Dominique; Ibos-Augé, Nathanaelle; Calvière, Lionel; Rogan, Christina; Labeyrie, Marc Antoine; Guichard, Jean Pierre; Godin, Ophélia; Kossorotoff, Manoelle; Habert, Marie Odile; Lasserve, Elisabeth Tournier; Chevret, Sylvie; Chabriat, Hugues
Abstract : Objective: To identify independent predictors of clinical or cerebral lesion progression in a large sample of adult patients with moyamoya angiopathy (MMA) prior to decisions regarding revascularization surgery. Methods: Ninety participants (median age, 37.5 years) were assessed at baseline and followed for a median time of 42.8 months. Incident ischemic and hemorrhagic strokes, death, as well as any incident ischemic and hemorrhagic lesions on MRI were recorded. Multiple demographic, clinical, and cerebral imaging measures at baseline were considered as potential predictors of clinical or cerebral tissue change at follow-up. Data were analyzed based on the Andersen-Gill counting process model, followed by internal validation of the prediction model. Results: Among multiple potential predictive measures considered in the analysis, Asian origin, a history of TIAs, and a reduction in hemodynamic reserve, as detected by imaging, were found to be significantly associated with an increased risk of combined clinical and imaging events. While the model estimated the risk of clinical or cerebral lesion progression to be approximately 0.5% per year when none of these factors was present, this risk exceeded 20% per year when all factors were present. Conclusion: A simple combination of demographic, clinical, and cerebral perfusion imaging measures may aid in predicting the risk of incident stroke and cerebral lesion progression in adult patients with MMA. These results may help to improve therapeutic decisions and aid in the design of future trials in adults with this rare condition.